The Status of Doctoral Education in the Council for Christian Colleges & Universities - Lawson, Kevin Ethan (Christian higher education, 2021)
The number of doctoral programs being offered by Christian universities is expanding, bringing new opportunities, needs, and challenges to these postsecondary institutions. Currently, 46 of the 113 governing member institutions of the Council for Christian Colleges & Universities (CCCU) offer doctoral-level programs. Of the 185 member, partner, and affiliate institutions connected with the CCCU, 76 (41%) offer doctoral-level education. This article reports on the results of a 2018 survey of 57 North American institutions affiliated with the CCCU regarding their doctoral programs, with particular attention to program design, faculty development and workloads, institutional infrastructure, and student needs. Recommendations are offered for the support of doctoral programs, faculty, and students.